Unusual Mortality Events of Harbor Porpoise Strandings in North Carolina, 1997–2009. (30th September 2013) - Hohn, Aleta A.; Rotstein, David S.; Byrd, Barbie L.
Abstract : A marked increase in the frequency of harbor porpoises ( Phocoena phocoena ) stranded in North Carolina in 2005 was declared as an Unusual Mortality Event (UME). Strandings occurred in January through May when harbor porpoises are seasonally present. Increased stranding rates were measured relative to a threshold to determine that the UME was occurring. The threshold analysis also revealed elevated strandings during 1999, an undeclared UME year. Recovered carcasses during 1999 and 2005 accounted for 39% of 261 strandings during 1997–2009. During 2005, of 43 strandings, primary or secondary causes of mortality included fishery interactions, emaciation, and interspecific aggression. Apart from small but significant differences in timing and condition of strandings, composition of strandings during UME and non-UME years was similar, with most being young-of-the-year and occurring during March and April, north of Cape Hatteras. Porpoises had high levels of parasitic infestation typical for this species. However, no indication of infectious disease and no cause of the 2005 event were found from gross and histologic findings. Response to UMEs is challenging, particularly along the expanses of North Carolina beaches, requiring additional effort to obtain carcasses in sufficiently fresh condition to determine the cause of these events.